High prevalence of vitamin D deficiency and insufficiency in adolescent inpatients diagnosed with eating disorders. Issue 6 (18th August 2014) - Modan‐Moses, Dalit; Levy‐Shraga, Yael; Pinhas‐Hamiel, Orit; Kochavi, Brigitte; Enoch‐Levy, Adi; Vered, Iris; Stein, Daniel
ABSTRACT Objective Previous studies assessing vitamin D status in adolescents with eating disorders showed inconsistent results. The aim of the current study was to assess vitamin D status in a large cohort of adolescent inpatients with eating disorders and its relation to bone mineral density (BMD) and depression. Method 25‐Hydroxyvitamin D (25OHD), calcium, phosphorus, and alkaline phosphatase levels as well as BMD and depression were assessed on admission in 87 inpatients (aged 16 ± 2 years, females = 81) with eating disorders [anorexia nervosa (AN) = 64; bulimia nervosa (BN) = 5; eating disorders not otherwise specified‐binge/purge type (EDNOS‐B/P) = 18]. Results Mean 25OHD levels were 24.1 ± 7.5 ng/ml (25.0 ± 7.6, 25.4 ± 9.9, and 22.0 ± 9.9 ng/ml in patients with AB, BN, and EDNOS‐B/P, respectively). Vitamin D deficiency (<15 ng/ml) was found in 7.8% of the patients, and insufficiency (15–20 ng/ml) in 22.2%. Only 16.7% had levels >32 ng/ml, considered optimal by some experts. No associations were found between 25OHD levels and BMD or comorbid depression. 25OHD levels during winter were significantly lower than summer levels (p < .001). Mean lumbar spine BMD z‐score in patients with AN and EDNOS‐B/P type was low (−1.5 ± 1.1) and correlated with body mass index standard deviation score (p = .03). Discussion Adolescents with eating disorders show a high prevalence of vitamin D deficiency and insufficiency. Given the risk of osteoporosis in this population, 25OHD levels found in this group may not offer optimal bone protection. Vitamin D levels should be routinely checked and supplementation should be administered as required. © 2014 Wiley Periodicals, Inc. (Int J Eat Disord 2015; 48: 607–614)